The majority of β-catenin mutations in colorectal cancer is homozygous - Arnold, Alexander; Tronser, Moritz; Sers, Christine; Ahadova, Aysel; Endris, Volker; Mamlouk, Soulafa; Horst, David; Möbs, Markus; Bischoff, Philip; Kloor, Matthias; Bläker, Hendrik (BMC cancer, 2020)
β-catenin activation plays a crucial role for tumourigenesis in the large intestine but except for Lynch syndrome (LS) associated cancers stabilizing mutations of β-catenin gene (CTNNB1) are rare in colorectal cancer (CRC). Previous animal studies provide an explanation for this observation. They showed that CTNNB1 mutations induced transformation in the colon only when CTNNB1 was homozygously mutated or when membranous β-catenin binding was hampered by E-cadherin haploinsufficiency. We were interested, if these mechanisms are also found in human CTNNB1 mutated CRCs.